Integrating Arts in a Collaborative Research Process: An Arts-Informed Inquiry (LEARNing Landscapes, 2022)
The rich learning that accompanies collaborative research practices can go unappreciated without systematic reflection and examination, which is an under-researched area. In this arts-informed inquiry, grounded in the experiences of four scholars, we show how artmaking was integrated into a qualitative research process to represent findings. In the qualitative phase, we analyzed researcher reflections kept throughout the research process to identify themes. Then, we created different art forms to represent the themes. Engaging in artmaking allowed us to be reflexive, strengthened our understanding of collaboration, and how using arts expanded the qualitative findings.
Keywords: arts-informed inquiry; collaborative research; arts in qualitative research; learning communities